Usage of Pediatric Emergency Department for Non-Urgent Complaints - Raziye Dut (Eurasian Journal of Emergency Medicine, 2017)

(untitled)
Aim: The number of visits to pediatric emergency departments is increasing. To determine the epidemiological profile of patients that are being examined by a pediatrician at emergency departments (EDs) is essential for planning medical care.Materials and Methods: 12.535 pediatric patients that had visited a pediatric emergency department (PED) due to a non-urgent complaint were enrolled. Demographic features such as gender and age; the nature of the presenting complaint; timing of the visit, i.e., frequency of the visits according to seasons, days of the week, times of the day; and other factors including admission rates, length of stay, and rates of treatment upon observation were reviewed.Results: Of the 12.535 patients included in the study, 5645 (45.0%) were girls, 6890 (54.9%) were boys, and the mean age was 4.9 years old. Most patients were 1-4y (33.8%) and patients older than 15y (3.2%) were the smallest group. The results revealed that the most common complaints were fever (38.5%), coughing (20.7%) and vomiting (11.1%). The inpatient admission rate was 0.69% and the rate of patients being treated upon observation was 5.9%. The most common visiting times were 18:00-23:59 (42.9%). Furthermore, 65% of visits took place during workdays and 35.0% during weekends. Most visits took place on Monday (15.5%). The length of stay was different amongst the different age groups (p=0.009).Conclusion: Pediatric patients typically are admitted to EDs for common pediatric complaints rather than uncommon complaints or accidents. The result of the present study may be useful in the management planning of pediatric emergency departments.